Towards Industrial Implementation: Experimental Campaign Based on Variations in Temperature, Humidity, and CO2 Concentration in Forced Carbonation Reactions of Recycled Aggregates - David Bastos; Catarina Brazão Farinha; Cinthia Maia Pederneiras; Rosário Veiga; José Alexandre Bogas; Ricardo Infante Gomes; António Santos Silva (Applied Sciences)
This research presents a sensitivity analysis of various parameters that affect the carbonation of recycled aggregates (RAs), namely CO2 concentration, temperature, and relative humidity. The range of parameter values is close to that found in cement plant chimneys with regard to the forced carbonation of RAs. With this purpose, the main characteristics of flue gas streams (CO2 concentration, temperature, and relative humidity) from two Portuguese cement plants were identified and used in this research. The results indicated that temperatures around 60 °C and CO2 concentrations around 25% accelerate the carbonation reaction and increase CO2 absorption in mixed recycled aggregates (MRAs). CO2 absorption consistently decreased as the relative humidity was reduced from 60% to 40%. The highest amount of CO2 captured was by a recycled concrete aggregate (RCA) in the conditions of 23 °C, 60% RH, and 25% CO2. Overall, the RAs were able to capture a significant amount of CO2, ranging from 52 to 348 kg of CO2 per tonne of cement paste, depending on the nature of the RA. These findings drawn from a parametric campaign provide valuable insights into the potential enforcement of carbonation for recycled aggregates under conditions that closely reflect those found in cement plants.